The painted veil - Maugham, W. Somerset (William Somerset), 1874-1965 (Vintage International, 2004)
Kitty Fane is the beautiful but shallow wife of Walter, a bacteriologist stationed in Hong Kong. Unsatisfied by her marriage, she starts an affair with Charles Townsend, a man whom she finds charming, attractive and exciting. But when Walter discovers her deception, he exacts a strange but terrible vengeance: Kitty must accompany him to his new posting in remote mainland China, where a cholera epidemic rages.